PEMBERDAYAAN USAHA KECIL BERBASIS POTENSI EKONOMI NAGARI SUNGAI KAMUYANG - Donard Games (Jurnal Pengabdian Warta Andalas, 2018)
The objective of this community service program is to enhance undertanding about theeconomic empowerment in Nagari Sungai Kamuyang. This is based on the nagari and regionaleconomic potential. The Prodi Management Team have visited the Nagari and provide some suggestionsand discussions with the leaders and economic actor of the nagari. In particular, the team from theManagement Program of Andalas University examine the effectiveness of small businesses in exploitingthe potential of the nagari through the empowerment of the Nagari Owned Enterprises (Bumnag). It hasbeen identified that the Kumuyang River has tremendous potential in the agricultural and tourismsectors. This could form a synergy which is expexcted to increase the level of the nagari economy.Community service program is also expected to provide knowledge for Wali Nagari, Bumnag managers,and local residents related to the management of the nagari economy.